Early Ecological Responses to Vegetation Enrichment for Pollinator Habitat Recovery using Tetragonula biroi in Community Agroforestry Systems - Masniawati, Andi; Suhri, Andi Gita Maulidyah Indraswari; Yusran; Hasdiansyah, Andi; Ruli, Fitha Febrilia; Riendriasari, Septiantina Dyah; Litaay, Magdalena (Jurnal Sylva Lestari, 2026)
Pollination decline has become a major ecological concern in tropical agroforestry systems, where habitat simplification reduces floral diversity and threatens pollinator stability. This study aimed to evaluate early ecological responses to vegetation enrichment designed to restore pollination function in a community-managed agroforestry landscape in South Sulawesi, Indonesia. A paired-plot experiment was established to compare two adjacent plots (each 0.25 ha), an enriched plot and a control plot, in which floral diversity, foraging activity, colony productivity, and microclimatic parameters were monitored from September to November 2025. Indices of diversity and comparative statistical tests were used to analyse ecological variables and assess treatment effects. Shannon-Wiener floral diversity indices (H') increased from 1.45 to 1.66 after vegetation enrichment, resulting in greater phenological overlap in relation to the control plots as well. These changes correspond to a substantially increased rate of stingless bee (Tetragonula biroi) visits and a higher return frequency in enriched plots (p < 0.05). An increase in foraging activity was observed, with a significantly greater extension of the brood area and a rise in honey production, reflecting improved colony performance. Also, microclimatic measurements indicated lower temporal variance in ambient temperature and light intensity under enriched vegetation, suggesting a dampening effect on more stable foraging conditions. In general, these results imply that small-scale vegetation can induce an early return to functioning through a trade-off effect on resource diversity, colony strength, and environmental stability in the context of community agroforestry systems and do not contradict community-based landscape management. Keywords: agroforestry, meliponiculture, pollination, Tetragonula biroi, tropical restoration, vegetation enrichment